Predictors and Consequences of Pregaming Using Day- and Week-Level Measurements - Barnett, Nancy P. (2013)
Drinking before going to a social event is common in adolescent and young adults and is associated with harmful outcomes, but information collected at the daily level is needed to better examine individual and contextual factors associated with pregaming. The purpose of this study was to investigate the prevalence of pregaming in a diverse sample of underage college students, demographic differences in rates of pregaming, the degree to which pregaming is associated with higher volume drinking, intoxication, and consequences, and the importance of time-of-year and day-of-week. Method: College students (N = 750) at three colleges completed past-week surveys throughout their freshman and sophomore years. Results: Pregaming was reported by three out of four drinkers and occurred on 31% of 12,361 drinking days. Compared to non-pregaming days, participants drank approximately two more drinks on pregaming days; this increase accounted for a .040 higher estimated blood alcohol concentration. Using Generalized Estimating Equations, we established that women, racial/ethnic minority students, and first-year students were more likely to pregame on a drinking day than males, non-Hispanic white students, and sophomore students, respectively. Men became more intoxicated on pregaming days and sophomores consumed more alcohol. Pregaming predicted higher positive and higher negative consequences, even after controlling for the number of drinks consumed. Pregaming was more common in the fall semester, in the early weeks of each semester, and on weekends. Prevention efforts targeting first-year students, the early weeks of the semester, and the hours before traditional party times may be effective at reducing this hazardous practice.